Analisis Efektivitas Komunikasi Digital Sebagai Media Komunikasi Di Masa Pandemi Covid-19 (Studi Kasus Pada PT Ellisa Kreatif Indokarya di Jakarta Pusat) - Heru Sudinta; Iwan Irwansyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
All sectors feel the impact of the corona virus outbreak e.g. education, economy, tourism and others. This has also shifted direct interpersonal communication system to digital media communication system (online). By the existence of Covid-19 virus, PT Ellisa Kreatif Indokarya Central Jakarta received a notice from the government to implement PSBB (Large-Scale Social Restriction) and to keep social distancing where all employees of PT Ellisa Kreatif Indokarya Central Jakarta are required to perform their work and day-to-day operations at home WFH (Work From Home). The purpose of this research is to identify and analyze the effectiveness, constraints and solutions of Digital Communication during covid-19 pandemic at PT Ellisa Kreatif Indokarya. This research is conducted by employing qualitative approach and descriptive method. The results from the research show the effectiveness of Digital Communication during the covid-19 pandemi (case study at PT Ellisa Kreatif Indokarya di Central Jakarta) with few constraints such as internet connection speed and task delivery or meeting affected PSBB (Large-Scale Social Restriction) as a government policy.